Maritrema orensense and Maritrema bonaerense (Digenea: Microphallidae): Descriptions, Life Cycles, and Comparative Morphometric Analyses - Alda, Pilar (2013)
Fil: Alda, Pilar. Centro de Estudios en Parasitología y Vectores (CEPAVE). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina